1986
DOI: 10.1111/j.1365-2605.1986.tb00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular volume, semen profile and serum hormone levels in fertile Thai males

Abstract: The fertility profile of 307 Thai male volunteers whose wives were currently in early pregnancy was established by genital examination, semen analysis and serum hormone analysis. Ninety percent of the subjects had testicular volumes of 12-25 ml (mean 17.2 ml) which was found to relate to body weight, height and the ponderal index as well as to the sperm count. However, values for semen analysis were significantly below the recognised standard for Caucasian males. There was an inverse relationship between testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 6 publications
7
40
1
Order By: Relevance
“…Because our azoospermic patients are non-obstructive, they have worst hormonal levels and Table 2 Chromosomal anomalies detected in the 115 patients smallest testicles (Table 1). These findings are consistent with those of previous reports [14,15]. Serum FSH, LH levels and testicular volume may have prognostic implications on testicular function, but we don't know whether these parameters have any prognostic implications on cytogenetic abnormality of infertile patients.…”
Section: Discussionsupporting
confidence: 91%
“…Because our azoospermic patients are non-obstructive, they have worst hormonal levels and Table 2 Chromosomal anomalies detected in the 115 patients smallest testicles (Table 1). These findings are consistent with those of previous reports [14,15]. Serum FSH, LH levels and testicular volume may have prognostic implications on testicular function, but we don't know whether these parameters have any prognostic implications on cytogenetic abnormality of infertile patients.…”
Section: Discussionsupporting
confidence: 91%
“…These mean that the testicular volumes of our study population were normal since we excluded patients with conditions known to strongly influence testicular volume. Several studies have been reported to prove the positive relationship between testicular volume and body weight (Aribarg et al, 1986;Ku et al, 2002;Bahk et al, 2010). In this study, both digit ratio and body weight had a significant correlation with testicular volumes in univariate analysis (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…Testis size reflects spermatogenesis because seminiferous tubules account for about 80% of the testicular mass, and it is generally considered as an index of reproductive function (spermatogenesis or semen analysis) (Aribarg et al, 1986;Takihara et al, 1987;Wu et al, 1993;Arai et al, 1998). Accordingly, reduction in testicular volume reflects decrease in the number of germ cells and seminiferous tubules (Lipshultz & Corriere, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the volume of the masks was calculated and summed to acquire total testes volume. One participant's testes volume measurement was excluded because his value was 2.8 SDs above the mean (mean = 38,064; SD = 11,183) and was more than 13,000 mm 3 larger than any recorded value found in the literature (30,(51)(52)(53). Of the more than 1,500 healthy, age-matched men in these studies, the largest reported value was 56,000 mm 3 , and this participant's measurement was 69,736 mm 3 .…”
Section: Methodsmentioning
confidence: 99%